2020
DOI: 10.1039/d0cp01715a
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of wettability alteration of the calcite {101̄4} surface

Abstract: We propose that formation of Na+ hydrates plays an important role in the wettability alteration of the calcite {101̄4} surface.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 43 publications
5
12
0
Order By: Relevance
“…Consistent with former investigations, 23,67 the importance of the positively charged Na + layer developed over a calcite plane as preferential adsorption sites for attracting anions and carboxylate head groups and binding them to the surface has also been observed in the present study. It should be emphasized that adsorption and localization of sodium cations on the CaCO 3 surface are in agreement with the nanoscopic experimental study by Ricci et al, who directly visualized the residence of Na + cations immediate to a calcite−solution interface.…”
Section: ■ Discussionsupporting
confidence: 93%
“…Consistent with former investigations, 23,67 the importance of the positively charged Na + layer developed over a calcite plane as preferential adsorption sites for attracting anions and carboxylate head groups and binding them to the surface has also been observed in the present study. It should be emphasized that adsorption and localization of sodium cations on the CaCO 3 surface are in agreement with the nanoscopic experimental study by Ricci et al, who directly visualized the residence of Na + cations immediate to a calcite−solution interface.…”
Section: ■ Discussionsupporting
confidence: 93%
“…In the literature, the adsorption of the water layer on calcite is characterized by two well-ordered water layers using the same force field and TIP3P water model. 32 The authors found that the two ordered water layers were located at 0.23 and 0.34 nm from the rock surface, which agrees with the experimental data 61 and other MD simulations. 36,62 These simulations were carried out in a NPT thermodynamics ensemble, under high temperature and pressure conditions (T = 363 K, P = 206 bar).…”
Section: ■ Results and Discussionsupporting
confidence: 79%
“…Li et al 32 examined the interaction of the monovalent and divalent ions with the calcite surface using ab initio and MD simulations. The authors reported the formation of two water hydration layers on the calcite surface that can only be penetrated by the monovalent (Na + and Cl − ) ions due to their hydration instability, while divalent cations (Ca 2+ and Mg 2+ ) could not penetrate the water layer due to their high dehydration-free energies thus remain in the bulk solution.…”
Section: ■ Introductionmentioning
confidence: 99%
“…[46] MD can be used to understand the interaction between different distillate/ heavy oil/asphalt and surfactants and is widely used to reveal the wettability changes of reservoir rocks at molecular scale. [47] Moreover, MD simulation can also study the influence of the polar head and hydrophobic tail structure of surfactant on dynamic contact change. [48] The MD simulation is developed based on the interaction between atomic force and atomic force field.…”
Section: Research On Stable Foammentioning
confidence: 99%